Climate change and allergic diseases: An overview - Singh, A. B.; Kumar, Pawan (Frontiers in Allergy, 2022)
Climate change has been regarded as a threat to the human species on the earth. Greenhouse gasses are leading to increased temperatures on Earth besides impacting the humanity. These atmospheric conditions have shown to alter the release pattern of pollens and can change the timing and magnitude of pollen release with flowering plants. As pollen is responsible for respiratory allergies in humans, so climate change can adversely affect human health in susceptible individuals. In this review, we highlight the association between climate change, increased prevalence and severity of asthma, and related allergic diseases. Increased air pollution can alter the production of local and regional pollen. This altered pattern depends on bioclimatic parameters. As simulated with a pollen-release model and future bioclimatic data, warmer temperatures lead to an increased pollen count in some specific locations and for longer periods. Thus, anticipation of a future allergic disease burden can help public health agencies in planning to develop strategies in mitigating the unprecedented health challenges expected in future years.